Pengaruh Endorse Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan : (Sensus Pada Pelanggan Aktif Celebrity Endorse Ria Noviara Nurhardiyanti) - Ria Noviara Nurhardiyanti (CV. ULIL ALBAB CORP, 2022)
This study aims to determine the effect of endorsement and service quality on customer satisfaction (Census on active customers Celebrity Endorse Ria Noviara Nurhardiyanti). The method used in this study is a quantitative method with a census approach. The population studied was 40 respondents who are active celebrity endorsers by Ria Noviara Nurhardiyanti. The data used is primary data where the data source directly provides data to data collectors. The tool used in this research is Multiple Linear Regression using SPSS software version 26. The results show that endorsement and service quality simultaneously have a significant effect on customer satisfaction with celebrity endorser Ria Noviara Nurhardiyanti. Partial endorsement has a significant effect on customer satisfaction celebrity endorser Ria Noviara Nurhardiyanti. Service quality partially has a significant effect on customer satisfaction celebrity endorser Ria Noviara Nurhardiyanti.